Kitāb al-Mawāhib al-ʿAliyyah fī al-Jamʿi Bayn al-Ḥikam al-Qur’āniyyah wa al-Ḥadīthiyyah (Book of high talents in the integration of Qur’anic and Hadith wisdom): a manuscript study - Akbar, Mohamed Aslam (IIUM Press, 2023)
This article is based on my doctoral study of an unpublished manuscript retrieved from the SMNA library 3 titled Kitāb al-Mawāhib al-ʿAliyyah fī al-Jamʿi bayn al-Ḥikam al-Qur’āniyyah wa al-Ḥadīthiyyah written by ‘Alī al-Muttaqī al-Hindī, a sixteenth-century Islamic scholar who authored Kanz al-ʿUmmāl (one of the most extensive Hadith compilations). The manuscript of Kitāb al-Mawāhib is a compendium of one thousand pieces of wisdom. Five hundred of them are from the Qur’an and the rest from the Hadith. The wisdom of Qur’an is identified in this manuscript as al-iqtisābāt (quotations) and Hadith as al-taḍmīnāt (inclusion or embodiment). This work is one of the earliest and most excellent compilations on wisdom ever made. It is an introduction to the virtue of wisdom to which the Qur’an refers as a great bounty in these words: “and he, to whom wisdom is granted, indeed has been granted abundant good”. The significance of the manuscript, as the author himself indicated, lies in four things, i.e., preserving the Qur’anic verses, conserving hadith narrations, commentary on the Qur’an, and special significance of Sufism. The author organized the collection of ḥikam (wisdom) in the Qur’an and Hadith according to the subject matter in the alphabetical order, such as Imān, Ihsān, Akhlāq, Imārah, and so on. He did this for every letter of the Arabic alphabet, from alif to yā. I was able to use the only copy available to me during my research. There are, however, another three manuscript copies of Kitāb al-Mawāhib available elsewhere: a handwritten copy at Maktabah Asʿad Afandī, Turkey; a handwritten copy at Maktabah Dāmād Zādah, Turkey; and a handwritten copy at Dār al-Kutub al-Miṣriyyah, Egypt. The details on these copies will be discussed in this article.